2016
DOI: 10.1200/jco.2016.34.2_suppl.2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hypofractionated high-dose intensity-modulated radiotherapy schedules for prostate cancer: Results from the phase III randomized CHHiP trial (CRUK/06/016).

Abstract: 2 Background: We aimed to explore the dose response relationship for two 3 Gray (Gy) hypofractionated radiotherapy (hRT) schedules for localised prostate cancer (PCa). Methods: hRT schedules of 60Gy/20 fractions (f) and 57Gy/19f were compared with conventional RT (cRT) 74Gy/37f; iso-effective for alpha-beta ratios of 2.5Gy and 1.5Gy respectively. The trial was powered to demonstrate non-inferiority between each hRT schedule and cRT, with 3,213 patients (pt) needed to rule out 5% inferiority (80% power, 1-side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Radical prostatectomy (RP) series indicated five-year recurrencefree survival rates between 65 and 84% [23] for intermediate-risk PCa. Modestly hypofractionated regimens report FFBF rates of 82 and 90% in low and intermediate risk respectively [18,24]. The current study demonstrates improved results compared to previously published data, regardless of modality.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Radical prostatectomy (RP) series indicated five-year recurrencefree survival rates between 65 and 84% [23] for intermediate-risk PCa. Modestly hypofractionated regimens report FFBF rates of 82 and 90% in low and intermediate risk respectively [18,24]. The current study demonstrates improved results compared to previously published data, regardless of modality.…”
Section: Discussionsupporting
confidence: 51%
“…Though the current analysis still did not meet the stoppage rules, we recommend using doses less than 50 Gy. The patients with toxicity required significant surgical intervention as a result of treatment and the probability of toxicity is not warranted given the safety of modest hypofractionation with ADT or lower doses of SBRT [18]. The Phase I study was designed to assess late toxicity at 9 months after radiation therapy however 4 of 6 late GI toxicities occurred greater than 9 months after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is particularly useful for patients who benefit logistically from a shortened HF course like patients living at long distance from an RT centre or who have a poor support system [57, 58]. The results of three recently published phase III trials are summarised in Table 2 [5961]. These trials revealed that HF is well tolerated, albeit with a slight increase in toxicity rates when compared to conventional schedules.…”
Section: Overview Of External Beam Radiation Treatmentsmentioning
confidence: 99%
“…[15][16][17] In addition, the recent phase III publications of this moderate hypo-fractionation regimen versus conventional fractionation showed non-inferiority in terms of biochemical control in a high-risk group. 18,19 In our institute, the schedule of 70 Gy at 2•5 Gy per fraction was adapted to treat localised prostate cancer at any level of risk in 2012. In this study we report the early results of moderate hypofractionation in 'high-risk' localised prostate cancer and evaluate the treatment results and toxicity of this regimen after implementation of this fractionation scheme for our population of patients.…”
Section: Introductionmentioning
confidence: 99%